Tuberculous bronchoesophageal fistula presenting with miliary tuberculosis: a case report - Khan, Zaara; Khanduri, Sachin; Rohit,; Sultana, Sadaf; Ahmed, Waquar; Dwari, Kunal; Ejaz, Shaista; Singh, Abhishek; Perumal, K. Prithvi; Yadav, Tushar; Chatterji, Upasana (International Journal of Research in Medical Sciences, 2024)
A 35-year-old Asian woman with no pre-existing illnesses presented with a chronic cough during eating, mucoid sputum production, low-grade fever, and significant weight loss over the past few months. She had no history of high-risk behavior, foreign body aspiration, or ingestion of toxic substances. Physical examination revealed mild pallor without other significant findings. Vital signs were normal. Laboratory tests indicated mild anemia, leukocytosis, and elevated ESR. Sputum AFB and viral/autoimmune markers were negative. The tuberculin skin test was positive. Imaging studies, including fluoroscopy with contrast and a CT scan of the thorax, identified an esophagobronchial fistula and miliary tuberculosis, with multiple diffuse lung nodules and associated changes. The CT scan showed a thick-walled fistulous tract connecting the esophagus to the right main bronchus at three points, along with miliary nodules and bronchiectatic changes. AFB staining of bronchial secretions was negative, but PCR and cultures confirmed M. tuberculosis. The patient was initiated on weight-adjusted antituberculosis therapy and nasogastric feeding. The patient showed significant symptomatic improvement after two months of antituberculosis treatment. This case underscores the importance of thorough diagnostic evaluation in atypical presentations of tuberculosis and highlights the potential for esophagobronchial fistulas to complicate pulmonary tuberculosis.